The Effect of Resilience on Mental Health Mediated by Perceived Social Support in Young Lecturers - Rosalinda, Irma; Indri Hapsari, Iriani; Mayangsari, Anggi; Yundianto, Devie; Khatami, Muhammad (Universitas Muhammadiyah Yogyakarta, 2025)
Young lecturers often face challenges at the start of their careers, including the demands of the Tridharma of Higher Education (research publications, teaching load, and community service), financial uncertainty, and heavy administrative burdens, which also impact their mental health. This study aims to investigate the role of resilience, mediated by perceived social support, on mental health. A cross-sectional study design was used with 170 young lecturers in Indonesia as participants. Using the Connor Davidson Resilience Scale (CD RISC) for Resilience, Mental Health Inventory (MHI-18) for Mental Health, and the Multidimensional Scale of Perceived Social Support (MSPSS) for Social Support. Preliminary analyses, including correlation, were conducted to confirm the relationships between the study variables. These tests established a significant total effect of Resilience, Social Support, and Mental Health. Next, Mediation analysis using bootstrapping was used as the analysis method through the PROCESS model 4 of SPSS v27.0 software. Results from the regression analysis revealed that Resilience (X) had a significant and positive total effect on Mental Health (Y). Further analysis testing the role of Social Support (M) revealed that it partially mediated this relationship. Resilience impacts Mental Health through two distinct pathways: (1) a significant direct effect (Resilience to Mental Health) and (2) a significant indirect effect (Resilience → Social Support → Mental Health), where Resilience enhances Social Support, which in turn improves Mental Health. Therefore, these findings offer valuable insights for institutions to enhance the well-being of young lecturers in Indonesia through systemic interventions, such as fostering a supportive work climate, implementing structured research mentoring programs between senior and junior lecturers, and promoting work-life balance.